FAKTOR PENYEBAB RENDAHNYA MINAT MAHASISWA PRODI MANAJEMEN DAKWAH DALAM BERWIRAUSAHA - Mail Hilian Batin (Prodi Magister Ekonomi Syariah FEBI UIN Raden Fatah Palembang, 2024)
Doing business at a young age is no stranger at this time, especially among students. Students who dare to take risks, especially in dividing their time between when they are in college and when they are looking for money, are the consequences that must be accepted. However, not all students are willing to take this risk, they are still overshadowed by some fears. This fear is called the factor causing the low interest of students in entrepreneurship. Respondents were 51 people who had not started a business before, out of a total of 66 students, they were distributed through 2 classes, namely the Dakwah Management class B and C. This type of research was field research by distributing question sheets that had to be filled out. The findings from this study are the dominant factors causing low interest in entrepreneurship are external factors including no capital, difficulty dividing time, and fear of failure.